Knowledge, Attitude, and Perceived Risks Towards COVID-19 Pandemic and the Impact of Risk Communication Messages on Healthcare Workers in Saudi Arabia - Mushi A; Yassin Y; Khan A; Yezli S; Almuzaini Y (Dove Medical Press, 2021)
Abdulaziz Mushi,1 Yara Yassin,1 Anas Khan,1,2 Saber Yezli,1 Yasir Almuzaini1 1The Global Centre for Mass Gatherings Medicine, Ministry of Health, Riyadh, Saudi Arabia; 2Department of Emergency Medicine, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Abdulaziz MushiPublic Health Directorate, Global Centre for Mass Gatherings Medicine, Ministry of Health, Riyadh, Saudi ArabiaTel +966506830492Email abhmashi@moh.gov.saPurpose: To investigate knowledge, attitude, and perceived risks towards COVID-19 pandemic among healthcare workers (HCWs) in Saudi Arabia. Besides, the impact of risk communication strategy on the attitude and practice of HCWs was investigated.Patients and Methods: We conducted a cross-sectional study that targeted HCWs from various Saudi health facilities. We utilized a self-administrated, online-based questionnaire designed to assess basic knowledge of COVID-19, attitude and disease perception, and the impact of risk communication messages among HCWs.Results: A total of 1691 responses were received in the study. The HCWs exhibited good levels of knowledge (total maximum score is 1) of COVID-19 concerning the modes of transportation of COVID-19 (0.82± 0.16), sample collection method for COVID-19 diagnosis (0.98± 0.08), transmission of infection from asymptomatic individuals (0.99± 0.11), and that antibiotics are not effective against the new COVID-19 (0.83± 0.38). Nearly one-third of the participants considered a high/very high possibility of acquiring COVID-19 infection. HCWs had good attitude scores concerning their willingness to deal with new COVID-19 patients (0.87± 0.33) and their beliefs in being educated on COVID-19 (0.99± 0.11). Almost all participants strongly agree/agree that it is important to take action to prevent the spread of COVID-19 within healthcare facilities and received health information messages. Notably, 93.4% of the participants stated that the received messages changed their attitude towards COVID-19 and its preventive measures. Good knowledge scores were significantly associated with age > 49 years old, higher educational level, and physician occupation. Similarly, good attitude scores were higher among males, HCWs aged 40- 49 years old, non-Saudi nationals, and physician and nurse occupations.Conclusion: HCWs have fair knowledge and attitude towards the COVID-19 pandemic. The risk communication is an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia.Keywords: COVID-19 pandemic, knowledge, attitude, risk communication, perceived benefits, Saudi Arabia